PúbliaTV, projeto de televisão escolar do Agrupamento de Escolas de Vila Viçosa - Gato, Lino; Padilha, José (Aprender, 2019)
PúbliaTV, projeto de televisão escolar do Agrupamento de Escolas de Vila Viçosa